Implementation of the use of plastic waste in Ecobricks for elderly school students in Bantul - Afrezah; Padmawati, Retna Siwi; Qaimamunazzala, Hayu (Universitas Gadjah Mada, 2022)
Purpose: This study aimed to analyze activities related to using plastic waste in ecobricks for elderly school students. Methods: This type of research is qualitative and has a case study design. The sampling technique used is purposive sampling. The data analysis used is thematic research. Results: The description of implementing plastic waste into eco-bricks, as well as the preparation, implementation, monitoring, and evaluation stages. The results of this eco-brick-making activity are assessed from the quantity, three or four eco-bricks a month; the quality results are the weight of the eco-bricks according to the standard, and they are made in the form of tables, chairs, and decorations, so that they are more valuable. Environmental changes have occurred since the existence of eco-bricks; no plastic waste is thrown carelessly, and no plastic waste is burned. Conclusions: Elderly school students have carried out eco-bricks-making activities so that they impact environmental health for the better.